Doing culture, doing business: The rise of a new entrepreneurial spirit in the Argentine creative industries - Beltran, Gaston Joaquin (2012)
This article seeks to understand the main characteristics of a new kind of agents and the role they played in the transformation of creative industries and how they assume an entrepreneurial status, focusing on the most dynamic spaces of Buenos Aires cultural production fields. It starts by identifying some structural features of the Argentine’s middle class and the latest transformations experienced by this sector, focusing on the impact of the economic crisis of 2001–2. It then analyses in depth the professional paths of some producers who started their businesses within that economic and social context and achieved high levels of recognition. These producers represent a new and unique type of entrepreneur.